Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solve the system by substitution 2x – 4y = –10 y = 4x + 6?
7 Answers
- 1 decade agoFavorite Answer
Substitute the phrase 4x+6 for "y":
2x-4(4x+6)= -10 (Parenthesis)
2x-16x-24= -10 (combine like terms)
-14x-24= -10 (isolate the variable by adding 24 to both sides)
-14x= 14 (divide both sides by -14)
x= -1
THEN>>>
substitue (-1) for x:
2(-1) - 4y = -10 (parenthesis)
-2 - 4y = -10 (add 2 to both sides)
-4y = -8 (divide both sides by -4)
y = 2
CHECK>>>
2(-1) - 4 (2) = -10
-2-8 = -10
-10 = -10
- Anonymous1 decade ago
2x - 4y = -10
y = 4x + 6
now recombination of eqns
1st : 2x = 4y - 10
2nd : 4x = y - 6
and multiple the 2nd eqn by -4 and plus with 1st eqn for nihilate the "y"
2x = 4y - 10
-4 ( 4x ) = -4 ( y - 6 )
then
2x = 4y - 10
-16x = -4y + 24
-14x = 14
divide by -14 both sides of eqn
x = -1
use the value of "x" at 2nd eqn
y = 4( -1 ) + 6 = -4 + 6 = 2
x = -1 , y = 2 ; S = ( -1, 2 )
as a result
- SivaLv 51 decade ago
2x – 4y = –10
In the place of y substitute y = 4x + 6
2x – 4(4x+6) = –10
2x – 16x-24 = –10
-14 x=-10+24
-14 x=14
x=14/-14
x=-1
substitute this x value in y=4x+6
y=4x+6
y=4(-1)+6
y=-4+6
y=2
- 1 decade ago
Follow my step below.
Firstly, give the first and second equation:
2x – 4y = –10y.....(1)
–10y = 4x + 6.....(2)
From (1), 2x – 4y = –10y
2x = –10y + 4y
2x = –6y
x = –3y.....(3)
Then substitute (3) into (2):
–10y = 4x + 6
–10y = 4(–3y) + 6
–10y = –12y + 6
–10y + 12y = 6
2y = 6
y = 3
Next, substitute y = 3 into (3):
x = –3(3)
x = –9
Therefore the answer must be:
x = –9 and y = 3
I hope you get the best answer for your question. Happy Halloween's Day too...
- artieLv 41 decade ago
As y = 4x + 6
we substitute y in the first equation and:
2x - 4*(4x+6) = -10
2x - 16x - 24 = -10
-14 = 14x
so x = -1
- Anonymous1 decade ago
As y = 4x + 6
2x - 4*(4x+6) = -10
2x - 16x - 24 = -10
-14 = 14x
x = -1
- someone elseLv 71 decade ago
substitute 4x+6 for y in eq1
2x-4(4x+6)=-10
2x-16x-24=-10
-14x=14
x=-1
y=4(-1)+6
y=2